Uncertainty in soil carbon accounting due to unrecognized soil erosion - Jonathan Sanderman; Adrian Chappell (Global Change Biology, 2013)
The movement of soil organic carbon ( SOC ) during erosion and deposition events represents a major perturbation to the terrestrial carbon cycle. Despite the recognized impact soil redistribution can have on the carbon cycle, few major carbon accounting models currently allow for soil mass flux. Here, we modified a commonly used SOC model to include a soil redistribution term and then applied it to scenarios which explore the implications of unrecognized erosion and deposition for SOC accounting. We show that models that assume a static landscape may be calibrated incorrectly as erosion of SOC is hidden within the decay constants. This implicit inclusion of erosion then limits the predictive capacity of these models when applied to sites with different soil redistribution histories. Decay constants were found to be 15–50% slower when an erosion rate of 15 t soil ha −1 yr −1 was explicitly included in the SOC model calibration. Static models cannot account for SOC change resulting from agricultural management practices focused on reducing erosion rates. Without accounting for soil redistribution, a soil sampling scheme which uses a fixed depth to support model development can create large errors in actual and relative changes in SOC stocks. When modest levels of erosion were ignored, the combined uncertainty in carbon sequestration rates was 0.3–1.0 t CO 2 ha −1 yr −1 . This range is similar to expected sequestration rates for many management options aimed at increasing SOC levels. It is evident from these analyses that explicit recognition of soil redistribution is critical to the success of a carbon monitoring or trading scheme which seeks to credit agricultural activities.